2013
DOI: 10.1021/es304339u
|View full text |Cite
|
Sign up to set email alerts
|

Re-Engineering an Artificial Sweetener: Transforming Sucralose Residuals in Water via Advanced Oxidation

Abstract: Sucralose is an artificial sweetener persistently present in wastewater treatment plant effluents and aquatic environments impacted by human activity. It has a potential to accumulate in the water cycle due to its resistance to common water and wastewater treatment processes. This study examined UV/H2O2 advanced oxidation and found that hydroxyl substitution of the chlorine atoms on the sucralose molecule can form a carbohydrate consisting of fructose and sugar alcohol, very similar to environmentally benign s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The half-life of SUC was up to 124 days in soil, 14 and its biodegradation potential in the aquatic environment was much lower. 7 Meanwhile, it has been reported that the transformation products of ACE can be more toxic than the parent compound. 15−17 to clarify the sources and mass loads of ASs to the environment in order to comprehensively evaluate their ecological risk.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The half-life of SUC was up to 124 days in soil, 14 and its biodegradation potential in the aquatic environment was much lower. 7 Meanwhile, it has been reported that the transformation products of ACE can be more toxic than the parent compound. 15−17 to clarify the sources and mass loads of ASs to the environment in order to comprehensively evaluate their ecological risk.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Advanced oxidation processes (AOPs) have been successfully applied for the treatment of wastewater [17][18][19][20][21][22] due to the fact that the hydroxyl radical (cOH) generated in AOPs can non-selectively oxidize most organic pollution. [23][24][25][26] However, the application of AOPs is currently not accepted because of expensive investment and operational problems. 3,4,12 Electrochemical technology has been widely investigated for the prevention and remediation of pollution because electrons are clean reagents.…”
Section: Introductionmentioning
confidence: 99%
“…where[SUC] 0 and[SUC] are the respective concentrations of sucralose at times and t, and k •OH,SUC is the second-order rate constant for the reaction of sucralose with •OH (k •OH,SUC =1.5-1.6•10 9 )(Keen and Linden 2013, Toth et al 2012).…”
mentioning
confidence: 99%